Desenvolvimento desigual e turismo no Brasil - Rita de Cássia Ariza da Cruz (Confins)
As a social, economic, cultural and spatial phenomenon, tourism in Brazil has been producing private geographies related to equipment and services such as operation and travel agency, hotel infrastructure, secondary residences, maritime cruises and, consequently, tourist flows through the national territory. These geographies of tourism in the country are understood, in this analysis, as the cause and the consequence of the so-called unequal development, as discussed contemporaneously by Smith (2008). In this sense, we seek, in addition to supposed cultural determinations, to understand, through a political economy of the territory, the spawning logic of the spatialities assumed by tourism as an economic activity in Brazil. Regarding the methodology of analysis, we seek in historical and dialectical materialism the bases for the interpretation of this complex phenomenon with an increasing social and economic importance, which is tourism. The notion of uneven development as a “systematic geographical expression of the contradictions inherent in the very construction and structure of capital” (Smith, 2008: 4) is the conceptual pillar on which we base our analysis. In addition, we consider that the notion of unequal development constitutes a central interpretative key to understand the place of tourism in the conflicting and contradictory process of production of space. As a result of this analysis, we highlight the significant spatial concentration of equipment and tourist flows in Brazil as historical products of processes of concentration and centralization of capital in its relationship with distinct Social and Territorial Labor Divisions distributed over time and materialized in space.